Se plaindre des enfants : positionnements épistémiques et rapports institutionnels dans les récits conversationnels entre au-pair et famille d'accueil - Pochon-Berger, Evelyne (My University, 2017)
The present study investigates how institutional relationships and identities are interactionally configured in a domestic context: the sojourn of an au-pair with a host family. While the au-pair regularly takes part in the family's ordinary life and becomes sort of a 'member' of the family over time, she is at the same time hired by the family as a childcare provider. Our study reveals that these institutional identities are oriented to by the participants, in particular during storytellings about the host family children's misconduct. The study is based on a corpus of 7 hours of dinner table conversations between Julie and her French-speaking host family. Drawing on Conversation Analysis, we show how, during storytelling, the au-pair and the host mother claim, display and negotiate their epistemic rights in relation to childcare in general or with these specific children.